Решите уравнение: (х-1)(х^2+4х+4)=4(х+2)

Решите уравнение: (х-1)(х^2+4х+4)=4(х+2)

1 ответ

  1. Решение:
    (x — 1)(x + 2)² = 4(x + 2)
    (x — 1)(x + 2)² — 4(x + 2)
    (x + 2)((x — 1)(x + 2) — 4) = 0
    (x + 2)(x² + 2x — x — 2 — 4) = 0
    (x + 2)(x² + x — 6) = 0
    x + 2 = 0, x1 = — 2
    x² + x — 6 = 0
    D = b² — 4ac(a = 1, b = 1, c = — 6)
    D = 1 — 4 * 6 = 25 = 5²
    x2, x3 = ( — b + — vD) / 2a
    x2 = ( — 1 — 5) / 2 = — 3
    x3 = ( — 1 + 5) / 2 = 2
    Ответ : x = — 3, x = — 2, x = 2.

Ответить

Ответить

Похожие вопросы